A Problem in Soviet Statistics - Bergson, Abram (The Review of Economics and Statistics, 1947)
gross output of Russian industry was approximately two hundred billion rubles. A rough calculation making use of the relation between the wage bill and all other costs in earlier years would suggest 220 billion as the more appropriate figure. Profits earned by industry amounted in I940 to I4.2 billion rubles.Y30 The total value of gross output could thus be estimated at about 234.2 billion rubles. Net output is assumed to have amounted to 55 per cent of gross output I or I28.8I billion 1940 rubles -I4.37 billion I94o dollars. This can be used to obtain a figure of 33.75 billion industrial dollars of I940 purchasing power